Buddhist Teachings for Achieving Success in Volunteer Work - Sattanawuth, Suchada; Phra Medhivajarapundit; Maechee Narumon Jiwattanasuk (The Journal of International Buddhist Studies College, 2025)
This qualitative study investigates how Buddhist teachings can foster success in volunteer work. The research had three objectives: (1) to define the key dimensions of success in volunteering, (2) to examine relevant Buddhist “peaceful means” that support successful volunteering, and (3) to propose a model that integrates those teachings into volunteer practice. Data were collected through documentary analysis and in-depth interviews with six key informants (experienced volunteers and Buddhist scholars). Using thematic content analysis, the study identified patterns that link inner development, ethical conduct, and sustained community engagement. Findings indicate that success in volunteer work is a holistic construct encompassing personal growth, meaningful social contribution, and congruence with ethical values, rather than solely organizational metrics or external recognition. Buddhist peaceful means, especially mindfulness (sati), the Four Brahmavihāras (loving-kindness, compassion, sympathetic joy, equanimity), and the Sangahavatthu (four bases of social harmony), emerge as both moral foundations and practical techniques that enhance emotional balance, compassionate action, and interpersonal harmony among volunteers. The study further proposes an integrative model that maps these Buddhist teachings onto Maslow’s Hierarchy of Needs, suggesting that addressing both psychological and ethical needs strengthens volunteer effectiveness, retention, and community impact. Implications for practice include incorporating mindfulness and brahmavihāra training into volunteer preparation, designing organizational cultures that support ethical development, and adopting policies that nurture volunteer well-being. The paper concludes by recommending empirical testing of the proposed model across diverse volunteer settings.